Feasibility of ESD-Based Teaching Materials Using EDP in Senior High School Physics on Alternative Energy and Environmental Issues - Wandira, Ayu Ramadani; Nuryadin, Atin; Zulkarnaen; Damayanti, Puardmi (Universitas Jember, 2025)
Twenty-first century education requires critical, creative, and solution-oriented thinking skills to address global issues such as environmental problems and the energy crisis. One approach that supports these skills is Education for Sustainable Development (ESD) integrated with the Engineering Design Process (EDP). This study aims to develop and evaluate the feasibility of ESD-EDP–based teaching materials on the topic of alternative energy in senior high school physics learning. This research is a type of Research and Development (R&D) using the ADDIE model, limited to the Analyze, Design, and Development stages. The Analyze stage included learning outcomes and student needs analysis, the Design stage produced the instructional framework, and the Development stage resulted in teaching materials validated by two subject matter experts, two media experts, and evaluated through the responses of 23 tenth-grade students. Validation results indicated very high feasibility with scores of 94% (content), 93% (presentation), 84% (language), and 92% (graphic design). Student responses averaged 88%, categorized as very good. Thus, ESD-EDP–based teaching materials are considered highly valid and feasible for senior high school physics learning on alternative energy topics.